Photocatalytic syntheses and evaluation of biological activities of rare disaccharides, 3-O-α-d-glucopyranosyl-d-arabinose - Sho Usuki; Pratiksha Babgonda Patil; Tiangao Jiang; Naoko Taki; Yuma Uesaka; Haru Togawa; Sanjay S. Latthe; Shanhu Liu; Kenji Yamatoya; Kazuya Nakata (Scientific Reports)
Abstract Recently, there has been a growing interest in rare sugars due to their potential applications in functional foods and pharmaceuticals. However, sustainable production methods for these compounds remain challenging due to their high cost, lengthy production times, and environmentally harmful reagents. Herein, we report a novel photocatalytic approach for synthesizing rare disaccharides from maltose, an abundant and renewable natural resource, under mild conditions at room temperature and atmospheric pressure using light as the energy source. The photocatalytic treatment of maltose using platinum compound-supported titanium oxide (PtCl/TiO₂) resulted in the formation of rare disaccharides, primarily 3-O-α-d-glucopyranosyl-d-arabinose and glucosyl-erythrose, which were characterized by HPLC, LC/MS, 13C NMR spectroscopy, and optical rotation measurements. Notably, biological evaluation of 3-O-α-d-glucopyranosyl-d-arabinose using HeLa and HEK293 cells demonstrated no cytotoxicity and negligible cellular uptake. Furthermore, enzymatic degradation studies using mouse intestinal α-glucosidase revealed significantly lower degradability compared to maltose, with minimal glucose production observed. These findings suggest that 3-O-α-d-glucopyranosyl-d-arabinose exhibits resistance to digestion and absorption in mammalian systems, highlighting its potential application as a low-calorie sweetener and a functional food ingredient. This study presents an environmentally benign synthetic route to rare disaccharides and demonstrates their promising biological properties.